Beyond the power of networks: Differentiating network structure from social media affordances for perceived social support. (June 2017) - Lu, Weixu; Hampton, Keith N
Existing research suggests that social media use is associated with higher levels of social capital—the resources contained within a person's network of friends, family, and other acquaintances. However, in predicting access to these resources, it has been impossible to distinguish the affordances of social media from the underlying advantage of maintaining a favorable social network of relationships on- and offline. Based on data from a representative, national survey, we compare the relationship between social network structure and various activities on Facebook for one type of resource: informal social support in the form of companionship, emotional support, and tangible aid. In addition to a positive association between number of close ties, overall network size and diversity and social support, we find that Facebook status updates and private messaging are independently associated with perceived support. We argue that these affordances are an outcome of the "pervasive awareness" provided by social media.